Brokering climate action: the UNFCCC secretariat between parties and non-party stakeholders - Saerbeck, B. (2020)
Our article aims to better understand the role of the secretariat of the United Nations Framework Convention on Climate Change (UNFCCC) in the increasingly complex global climate governance structure. We employ an innovative approach to addressing this issue by systematically examining the climate secretariat’s relations with the main groups of actors involved in this policy domain, in particular with nonparty actors. In a first step, we use social network analysis (SNA) to examine the secretariat’s relations with nonparty and state stakeholders and to identify its position in the UNFCCC policy network. An understanding of where the climate secretariat stands in the global climate governance network and which actors it interacts with most allows us to draw preliminary conclusions about the ways in which it connects with other stakeholders to influence global climate policy outputs. In a second step, we conduct thirty-three semistructured interviews to corroborate the results of the SNA. Our findings lend support to the argument that the climate secretariat may gradually be moving from a rather neutral and instrumental stance to playing a proactive and influential role in international climate governance. It aims to increase its political influence by establishing strategic links to actors other than the formal negotiation parties.